2020
DOI: 10.1002/jsfa.10588
|View full text |Cite
|
Sign up to set email alerts
|

Yeast population dynamics during spontaneous fermentation of icewine and selection of indigenous Saccharomyces cerevisiae strains for the winemaking in Qilian, China

Abstract: BACKGROUND: Icewine produced in China is becoming popular, but there is only limited knowledge available on the yeast population that occurs during fermentation and also on the selection of indigenous Saccharomyces cerevisiae strains for its production. In this work, we first investigated yeast species and the evolution of yeast population in spontaneous fermentations of icewine produced in the Qilian region of China and then analyzed the biodiversity and important enological properties of S. cerevisiae isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Both M. pulcherrima YC12 and R. lusitaniae QTX15 significantly increased the concentrations of heptanoic acid, hexanoic acid, and nonanoic acid; and R. lusitaniae QTX15 also significantly increased the concentration of acetic acid. A high concentration of volatile acetic acid can produce a cat urine taste in wine, which deleteriously affects the aroma quality [ 2 ]. Canonico et al [ 61 ] reported that the concentration of acetic acid in beer produced by mixed fermentation was significantly higher than that produced by pure culture with T. delbrueckii .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both M. pulcherrima YC12 and R. lusitaniae QTX15 significantly increased the concentrations of heptanoic acid, hexanoic acid, and nonanoic acid; and R. lusitaniae QTX15 also significantly increased the concentration of acetic acid. A high concentration of volatile acetic acid can produce a cat urine taste in wine, which deleteriously affects the aroma quality [ 2 ]. Canonico et al [ 61 ] reported that the concentration of acetic acid in beer produced by mixed fermentation was significantly higher than that produced by pure culture with T. delbrueckii .…”
Section: Resultsmentioning
confidence: 99%
“…The colonies of S. cerevisiae F33 were smooth and creamy white, whereas those of H. uvarum QTX22 and R. lusitaniae QTX15 were smooth and green, those of S. crataegensis YC30 and P. kluyveri HSP14 were white with flocculent folds, and that of M. pulcherrima YC12 was milky white, and could be easily discriminated from S. cerevisiae F33 in mixed cultures on WL media. Fermentation rate was calculated as the loss of CO 2 (g/L) within 24 h during the fermentation [ 2 ]. After fermentation, all wine samples (350 mL) were centrifuged for 8 min (4000× g , 4 °C), and the cell-free supernatants were stored at −20 °C and used within 6 months for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeast cell wall polysaccharides have been used as thickeners, emulsi ers, preservatives and anticoagulants in food additives to improve the avor and stability of food [21][22][23]. In addition, yeast mannoprotein has several advantages in improving wine quality, it can prevent turbidity, reduce astringency, retain aroma components, and stimulate the growth of lactic acid bacteria [24]. Therefore, mastering the role of genes related to the cell wall of S. cerevisiae can modify the characteristics of yeast and optimize the fermentation process, which is of great signi cance to the food, medicine and fermentation industries [25].…”
Section: Discussionmentioning
confidence: 99%